Association of serum selenium with MASLD and liver fibrosis: A cross-sectional study. - Wenying Guo; Ting Weng; Yufei Song (PLoS ONE)
Background The evolution of NAFLD, MAFLD, and MASLD underscores significant advancements and nomenclatural shifts in the realm of chronic liver disorders. This study primarily aimed to investigate the possible link between serum selenium levels and the occurrence of MASLD. Methods Utilizing data from NHANES for the years 2017 through 2020, we performed an in-depth analysis. To evaluate the relationship between serum selenium concentrations and the prevalence of MASLD and liver fibrosis, we employed a comprehensive multivariable analysis. This approach accounted for a range of variables to enhance the robustness and reliability of our results by mitigating potential confounding factors. Results Through the application of linear regression models, our comprehensive data analysis revealed significant insights. Elevated serum selenium levels exhibited a distinct positive correlation with CAP, whereas an inverse relationship with LSM was observed. Multivariate logistic regression analysis indicated that higher serum selenium concentrations were significantly associated with an increased likelihood of MASLD, alongside a marked reduction in the probability of liver fibrosis. Conclusion The findings of this study highlight a significant positive association between elevated serum selenium levels, CAP, and the prevalence of MASLD, coupled with an inverse relationship with LSM and liver fibrosis.